2D/2D atomic double-layer WS₂/Nb₂O₅ shell/core nanosheets with ultrafast interfacial charge transfer for boosting photocatalytic H₂ evolution - Lin, Bo (2022)
Low-efficiency charge transfer is a critical factor to limit the photocatalytic H2 evolution activity of semiconductor photocatalysts. The interface design is a promising approach to achieve high charge transfer efficiency for photocatalysts. Herein, a new 2D/2D atomic double-layer WS2/Nb2O5 shell/core photocatalyst (DLWS/Nb2O5) is designed. The atom-resolved HAADF-STEM results unravel the presence of an unusual 2D/2D shell/core interface in DLWS/Nb2O5. Taking advantage of the advanced femtosecond-resolved ultrafast TAS spectra, the average lifetime of charge carriers for DLWS/Nb2O5 (180.97 ps) is considerably shortened as compared to that of Nb2O5 (230.50 ps), strongly indicating that the 2D/2D shell/core interface enables DLWS/Nb2O5 to achieve ultrafast charge transfer from Nb2O5 to atomic double-layer WS2, thus yielding a high photocatalytic H2 evolution rate of 237.6mmol/h, up to 10.8 times higher than that of pure Nb2O5 nanosheet. This study will open a new window for the development of high-efficient photocatalytic systems through the interface design.